Anatomical changes, osmolytes accumulation and distribution in the native plants growing on Pb-contaminated sites (2020)
Native plants growing on heavy-metalcontaminated sites are the potential candidates for phytoremediation of contaminated sites due to their tolerance and adaptation to toxic environment. For better application of the technology, in-depth knowledge and understanding of the anatomy and physiology of these plant species are essential. In this study, anatomical changes in roots and leaves of various plant species growing on Pb-contaminated sites as well as osmolytes (proline, PR; glycine betaine, GB; and phenolics, PH) production and distribution in different plant parts were investigated. The soil and plant samples were collected in triplicates from two different Pb-contaminated sites, while control plants were collected from the University of Ibadan. The plants were washed and partitioned into different parts for anatomical and biochemical studies, and soil adhering to the roots of different plant species was collected for the determination of Pb contents. Sporobolus pyramidalis, Cynodon dactylon, Imperata cylindrica, Eleusine indica, Gomphrena celosioides, Rhinconspora corymbosa and Echinochloa colona are the plant species common to these contaminated sites. Though with variations based on the site, thick epidermis and sclerenchyma, pronounced and numerous vascular bundles as well as trichomes were some of the anatomical characteristics of these metallophytes from contaminated sites compared to their counterparts from uncontaminated site. These plants also produced PR, GB and PH, with PH being the highest followed by PR and GB. Accumulation in different parts of the plants also varied depending on the plant species and the osmolyte. They were more in the leaf than other plant parts. Among the plant species, Sporobolus pyramidalis had the highest value of proline (3.26 and 2.63 lg/g FW) and glycine betaine (3.44 and 2.23 lg/FW) in the leaf and stem, respectively, followed by Cynodon dactylon having 2.20 and 0.89 lg/g FW proline and 2.02 and 0.94 lg/g FW glycine betaine. On the Pb accumulation in plant, more lead (Pb) was found in the roots than other plant parts. Gomphrena celosioides accumulated the highest Pb (4537.50 and 1081.50 mg/kg) in the root and shoot, respectively, followed by Eleusine indica (3988 and 699.00 mg/kg), while the lowest values were recorded for Echinochloa colona (36.87 and 5.97 mg/kg). In rhizospheric soils, G. celosioides had the highest Pb content (34,405.00 mg/kg) which was higher than other rhizospheric soils. In conclusion, phenolics were produced more in these metallophytes and all the osmolytes were more in leaf than root. Anatomical modifications in response to heavy metal exposure differed between plant species and level of contamination. Lead accumulation in plant also varied depending on plant species.